Urban and suburban COVID-19 immunization: comparison of experiences at Parit Sulong and Puncak Alam / Mawaddah Azman ... [et al.] - Azman, Mawaddah; Gendeh, Hardip Singh; Mohamad, Mohd Shawal Firdaus; Wan Mohd Zohdi, Wan Najwa; Md Noor, Julina; Jarmin, Razman; Harunarashid, Hanafiah (Faculty of Medicine, 2024)
Introduction: Malaysia boasts a diverse geographical distribution ranging from urban, suburban and rural areas. The COVID-19 national immunization program calls for specific strategies to enhance vaccine roll-out. Methods: A retrospective study was conducted at two vaccination centres in Parit Sulong and Puncak Alam. Registration data from 150 and 1420 consenting adults receiving their first dose of COVID-19 vaccination from Parit Sulong and Puncak Alam were included, respectively. Results: The vaccination center at Parit Sulong utilised three methods: 1) satellite vaccination camp; 2) mobile outreach camp; and 3) hometo-home visits to improve vaccine reach in a rural district. The vaccination center at Puncak Alam utilised two methods: 1) vaccination in a large hall; and 2) drive-through vaccination to enhance daily vaccine administration in an urban district. The vaccine recipients at Parit Sulong were significantly older compared to Puncak Alam (70.39 SD 11.39 vs 51.52 SD 11.02 years) (p<0.0001). A significantly higher proportion of vaccine recipients at Parit Sulong were unable to read or write in their mother tongue (41.33%)(p<0.0001), do not own a mobile phone (53.33%)(p<0.0001) and do not have access to MySejahtera mobile application(84.57%)(p<0.0001). Conclusion: The mobile vaccination model allows for greater vaccination reach and administration, targeting suburban and rural residents with transportation and technology restrictions. The drive-through vaccination model improved the vaccine uptake among young families with children, heavily pregnant ladies and elderly with physical limitations living in urban areas who have access to MySejahtera.